KORELASI LAJU EKSKRESI ALBUMIN DENGAN PARAMETER DISFUNGSI ENDOTEL PADA PENDERITA DIABETES MELITUS TIPE 2 DENGAN MIKROALBUMINURIA - , dr. Niniek Yusida, Tahono, dr. Sp.PK-K ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Diabetes mellitus is a chronic metabolic disorder, characterized by impaired metabolism of carbohydrates, fats and proteins, followed by macro-and microvascular complication. Endothelial dysfunction has been reported in patients with type 2 diabetes and also in people with type 1 diabetes who showed microalbuminuria. Some parameters that can be used as a marker of endothelial disfunction is soluble Vasculer Cell adhesion molecule (sVCAM-1), plasminogen activator inhibitor-1 (PAI-1), von Willebrand factor and microalbuminuria (MAU). The purpose of this study is to determine whether there is a correlation between albumin excretion rate with others endothelial disfunction parameters (sVCAM-1 and vWF) in type 2 diabetes patients with MAU. This study used cross-sectional study design, study subjects is type 2 diabetes patients with MAU, who come to Endocrinology Subdivision of Internal Medicine Departement and Laboratory of Clinical Pathology at dr. Moewardi Hospital Surakarta. Statistical analysis using Pearson or Spearman correlation test (r),and linier correlation regression. Significant if p <0.05 with 95% confidence interval. Albumin excretion rate can be correlated with endothelial dysfunction parameters (sVCAM-1 and vWF), which occurs in type 2 diabetics with MAU. This has important implications both in the clinic and epidemiology, because endothelial dysfunction is a risk factor towards cardio vascular complications, and urinary albumin excretion rate examination to detect the present of MAU is easier, cheaper and can be carried out routinely in the laboratory